ANALISIS KEBIJAKAN PEMERINTAH REPUBLIK INDONESIA ERA KEPEMIMPINAN PRESIDEN JOKO WIDODO - Desi Ratna Sari; Rani Anggriani; Restu Zebua; Sylvia Maria Pasaribu; Yediza Saputrinta (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
The reform period became an era that was quite important for Indonesia because it was followed by rapid progress and development. During the reform period, there were several presidents who led this country with various characteristics and policies implemented for the betterment of the nation, including B.J Habibie, Abdurrahman Wahid, Megawati Soekarnoputri and Susilo Bambang Yudhoyono. Currently the Indonesian government is being led by President Joko Widodo who is trusted by the public to lead Indonesia for two terms. This study aims to reveal various policies and characteristics of President Joko Widodo's leadership, especially in the fields of politics, law, socio-culture, economy, defense-security, and education. The method used in this research is the historical method and the source of the article is obtained through a literature study that is relevant to the topic raised. The results of the research show that President Joko Widodo's government has produced many positive results for the progress and development of Indonesia, especially during the current reformation period.